1997
DOI: 10.1021/om961077s
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of Trindane:  Possible Precursors of Sumanene

Abstract: Trindane (the condensation trimer of cyclopentanone) yields complexes of the type (η6-trindane)ML n , where ML n = Cr(CO)3 (6), Mo(CO)3 (8), Mn(CO)3 + (9), or (C5H5)Fe+ (10a,10b). X-ray crystallographic data are reported for (η6-trindane)Cr(CO)3 (6) and show that the three five-membered rings adopt envelope conformations in which the central methylene groups are bent toward the metal. When the chromium complex 6 is stirred with DMSO-d 6 in the presence of t-BuOK, up to 12 benzyl protons can be exchanged for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…This molecule forms zig-zag chain-like stacks of the form -A-B-A-B-, as shown in Figure 2 b, where the core separation distance between the neighboring molecules is more than 3.9 . Although we could not get single crystals of 9 that were suitable for X-ray diffraction, the crystal structure for its hexa(1-propoxy) analogue (11) has been solved. [22] This compound exhibits a so-called "flyingsquirrel-like" molecular structure [23] and forms the columnar stack ( Figure S4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule forms zig-zag chain-like stacks of the form -A-B-A-B-, as shown in Figure 2 b, where the core separation distance between the neighboring molecules is more than 3.9 . Although we could not get single crystals of 9 that were suitable for X-ray diffraction, the crystal structure for its hexa(1-propoxy) analogue (11) has been solved. [22] This compound exhibits a so-called "flyingsquirrel-like" molecular structure [23] and forms the columnar stack ( Figure S4).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with 1, sumanene 2 is a more strained buckybowl, [10] and its chemical synthesis is thus more challenging owing to higher strain energy for the ring cyclization. Several approaches to 2 have been attempted since 1993, [11] but the first successful synthesis was accomplished by Sakurai et al in 2003. [12] Subsequent investigation indicated that this new buckybowl system shows interesting features for coordination chemistry [13] and as electronic materials.…”
mentioning
confidence: 99%
“…Although, the interest in the sumanene chemistry arise in 1993 when for the first time Mehta and co-workers reported the unsuccessful attempt towards the construction of this beautifully simple yet much valuable π-conjugated buckybowl. Four years later, McGlinchey’s group has tried to synthesize it by means of an organometallic precursor but they also did not make available the breakthrough for the research community [ 70 71 ]. On the other hand, four years before to the Mehta’s report, Klemm and co-workers attempted to synthesize trithiasumanene 151 [ 72 ] from triphenylene 139 but they could obtain merely mono- and di-bridged systems and no required product was observed ( Scheme 38 ) [ 73 ].…”
Section: Reviewmentioning
confidence: 99%
“…Attempts to synthesize 1 based on an approach involving the construction of three five‐membered rings using a planar precursor with a triphenylene skeleton have failed . Other approaches using trindane or trindene derivatives as precursors have also been proposed, but the synthesis of 1 has not been achieved. The construction of a three‐dimensional framework followed by oxidative aromatization provided a solution .…”
Section: Synthesis and Structure Ofmentioning
confidence: 99%